EIGHT NEW RECORDS OF ZINGIBER MILL. (ZINGIBERACEAE) FOR THE FLORA OF LAO P.D.R. - Souvannakhoummane, K.; Leong-Škorničková, J. (Edinburgh Journal of Botany, 2017)
Eight Zingiber species (Z. densissimum S.Q.Tong & Y.M.Xia, Z. kerrii Craib, Z. ligulatum Roxb., Z. nudicarpum D.Fang, Z. orbiculatum S.Q.Tong, Z. parishii Hook.f. subsp. phuphanense Triboun & K.Larsen, Z. recurvatum S.Q.Tong & Y.M.Xia and Z. smilesianum Craib) are newly recorded for the flora of Laos, raising the total number of species to 25. Colour illustrations, notes on their distribution, and citations of the specimens supporting the new records are given, as well as vernacular names and uses. An updated checklist of Zingiber in Laos, with an indication of the current sectional placement of each species, is presented.
Keywords: Ethnobotany; Zingiber densissimum; Zingiber kerrii; Zingiber ligulatum; Zingiber nudicarpum; Zingiber orbiculatum; Zingiber parishii subsp. phuphanense; Zingiber recurvatum; Zingiber smilesianum